Characterization of Natural Clay from Tulungagung Regency, East Java Province, Indonesia - Rahayu, Mike; Sholeha, Novia Amalia; Rahmah, Siti (Department of Chemistry Faculty of Science and Technology Walisongo, 2023)
Natural clay is a material that has various benefits and is abundant in the environment. This research will study about the characteristics of natural clay from Tulungagung, East Java, Indonesia. This research used two samples of Natural Clay-1 (NC-1) and Natural Clay 2 (NC-2) from Tulungagung, Sidem village, Gondang district. The natural clays were dried at room temperature for 2 days then pulverized and sieved using 100 mesh sieves. X-ray diffraction (XRD), x-ray fluorescence (XRF), infrared spectroscopy (IR), and scanning electron microscopy (SEM) have been utilized to characterize the natural clay. XRF analysis revealed that the primary components of Tulungagung's natural clay are Fe, Si, and Al. Montmorillonite, quartz, and anatase are the primary natural clay minerals, as determined by XRD and FTIR. The results of the SEM indicate a non-uniform material surface.